Beyond Productivity: How Generative AI Reshapes Creativity, Critical Thinking, and Personalized Learning in Higher Education - Kms. Badaruddin (Nurul Jadid University, 2025)
Higher education has changed dramatically because to GenAI. Academic productivity remains the focus of most studies. The study examines how GenAI transforms creativity, critical thinking, and individualized learning from a Beyond Productivity perspective. This study used qualitative case study design. In-depth interviews, observations, and document analysis of GenAI-using professors and students provided data. The Miles, Huberman, and Saldaña interactive approach was used for data analysis, including condensing, presenting, and extracting conclusions from triangulation of sources and approaches. Two significant findings emerged from the investigation. GenAI helps students develop creativity, critical thinking, introspection, and knowledge construction by shaping human-AI co-creation. GenAI creates an adaptable and personalized learning ecosystem by providing real-time feedback, personalised learning support, and self-regulated learning. This study establishes GenAI as a productivity tool and a catalyst for higher education cognitive and pedagogical change. This finding affects how higher education institutions create AI learning strategies and policies to develop 21st-century competences.